2017
DOI: 10.21475/ajcs.17.11.10.pne603
|View full text |Cite
|
Sign up to set email alerts
|

Artificial vernalization in strawberry plants: phyllochron, production and quality

Abstract: To obtain the best productive performances strawberry plants require an accumulation of cold hours which varies by cultivar; this project evaluated phyllochron, the quality and fruit production from vernalized and non-vernalized seedlings of the strawberry cultivars Albion and Camarosa. The treatments consisted of seedling vernalized before planting for 200 cold hours in a cold chamber with temperatures 4.0 ºC. Seedlings in the control treatments were not vernalized and were transplanted directly after arrival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…These results agreed with Oliveira and Scivittaro (2009), who reported that vernalizing transplants for 21 days (around 500 hours of cold) optimized yield and the number of strawberry fruits per plant. Diel et al (2017) also found that vernalization increased fruit production by the Camarosa and Albion varieties.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…These results agreed with Oliveira and Scivittaro (2009), who reported that vernalizing transplants for 21 days (around 500 hours of cold) optimized yield and the number of strawberry fruits per plant. Diel et al (2017) also found that vernalization increased fruit production by the Camarosa and Albion varieties.…”
Section: Resultsmentioning
confidence: 79%
“…This indicated that vernalization improved fruit production and confirmed the results obtained by Oliveira and Scivittaro (2009), who also obtained a higher yield with vernalized transplants when the Camarosa variety was used. Diel et al (2017), who also used Camarosa, found that the average yield from vernalized plants was 1007.50 g plant -1 but only 774.16 g plant -1 for non-vernalized plants. However, no differences were found between the vernalized and non-vernalized plant yields when the Albion variety was tested (207.10 and 196.91 g plant -1 , respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Para tratar de contribuir a mejorar las condiciones de producción del cultivo de fresa en Guanajuato, en el último lustro se han desarrollado variedades de fresa adaptadas a la región agroclimática de la región que presentan mayor rendimiento y características organolépticas ; no obstante, la propagación de las mismas sigue presentando problemas fitosanitarios lo que dificulta la adopción de estos materiales por los productores. Para asegurar la obtención de plantas libres de enfermedades, de mayor vigor y con alta pureza genética la propagación in vitro, representa una alternativa viable, que en fresa ha sido muy estudiada (Calvete et al, 2009;Rekha et al, 2013;Ling and Wetten, 2017;Diel et al, 2017).…”
Section: Introductionunclassified